Risk Factors of Cardiovascular Death after Venous Thromboembolism: Results from a Prospective Cohort Study - Noumegni, Steve Raoul; Mansourati, Vincent; Tromeur, Cécile; Mao, Raphael Le; Hoffmann, Clément; Moigne, Emmanuelle Le; Nasr, Bahaa; Gentric, Jean-Christophe; Guegan, Marie; Poulhazan, Elise; Bressollette, Luc; Lacut, Karine; Couturaud, Francis; Didier, Romain (Thrombosis and Haemostasis, 2022)
Background Cardiovascular deaths (CVDTs) are more frequent in patients with venous thromboembolism (VTE) than in the general population; however, risk factors associated with this increased risk of CVDT in patients with VTE are not described.Methods To determine the risk factors of CVDT in patients with VTE from a multicenter prospective cohort study, Fine and Gray subdistribution hazard models were conducted.Results Of the 3,988 included patients, 426 (10.7%) died of CVDT during a median follow-up of 5 years. The risk factors of CVDT after multivariate analyses were: age of 50 to 65 years (vs. <50 years, hazard ratio [HR]: 3.22, 95% confidence interval [CI]: 1.67–6.62), age >65 years (vs. <50 years, HR: 7.60, 95% CI: 3.73–15.52), cancer-associated VTE (vs. transient risk factor-related VTE, HR: 1.73, 95% CI: 1.15–2.61), unprovoked VTE (vs. transient risk factor-related VTE, HR: 1.42, 95% CI: 1.02–2.00), past tobacco use (vs. never, HR: 1.43, 95% CI: 1.06–1.94), current tobacco use (vs. never, HR: 1.87, 95% CI: 1.15–3.01), hypertension (HR: 2.11, 95% CI: 1.51–2.96), chronic heart failure (HR: 2.28, 95% CI: 1.37–3.79), chronic respiratory failure (HR: 1.72, 95% CI: 1.02–2.89), and atrial fibrillation (HR: 1.67, 95% CI: 1.06–2.60). The risk of CVDT was significantly reduced with direct oral anticoagulants (vs. vitamin-K antagonists) and with longer duration of treatment (>3 months).Conclusion Risk factors of CVDT after VTE include some traditional cardiovascular risk factors and other risk factors that are related to characteristics of VTE, and patients' comorbidities.
Keywords: venous thromboembolism; cardiovascular deaths; cardiovascular mortality; risk factors; predictor; prospective cohort